2007
DOI: 10.1080/01446190701598681
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of craft workers' and foremen's perceptions of the factors affecting construction labour productivity

Abstract: Extensive studies have been conducted to examine the factors affecting construction productivity, but efforts have rarely been made to obtain craft workers' input. A survey was administered to 1996 craft workers throughout the US to quantify the workforce's perspective of construction labour productivity. Specifically, the survey measured the impact of 83 productivity factors, which had been identified through 18 focus group sessions with craft workers and their immediate supervisors on jobsites located throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 17 publications
0
49
0
4
Order By: Relevance
“…Results at the 95% confidence level indicate that the PM and trade groups perceived some parameters' influences on CLP very differently. Statistically significant differences were reported between different generations of craft workers (Dai and Goodrum 2012), foremen and craft workers (Dai et al 2007), union and nonunion craft workers, and trades (Dai et al 2009). Eslamdoost and Heravi (2013) also observed similar differences among office and site staff respondents in comparing the rankings of factors influencing CLP.…”
Section: Comparison Of Perspectives On Parameters Between Project Manmentioning
confidence: 94%
See 3 more Smart Citations
“…Results at the 95% confidence level indicate that the PM and trade groups perceived some parameters' influences on CLP very differently. Statistically significant differences were reported between different generations of craft workers (Dai and Goodrum 2012), foremen and craft workers (Dai et al 2007), union and nonunion craft workers, and trades (Dai et al 2009). Eslamdoost and Heravi (2013) also observed similar differences among office and site staff respondents in comparing the rankings of factors influencing CLP.…”
Section: Comparison Of Perspectives On Parameters Between Project Manmentioning
confidence: 94%
“…In the most extensive and detailed existing study of factors influencing CLP, Dai et al (2009) carried out a factor survey based on an identified 83 factors with 1996 craftspeople on 28 U.S. industrial construction projects to identify the top 10 critical factors and the relationship between these factors. Detailed investigation of differences in perception between the different generations of craft workers (Dai and Goodrum 2012), foremen and craft workers (Dai et al 2007), union and non-union craft workers, and trades (Dai et al 2009) was carried out using the same survey data; significant differences were observed between the compared groups. Jarkas and Bitar (2012) identified 45 factors grouped under four categoriestechnological, human/labour, management, and external-and conducted a questionnaire survey with 157 practitioners from building and civil engineering construction firms in Kuwait; this study established the relative importance of the identified 45 factors and four factor categories.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As efforts have been rarely been made to obtain craft worker' input to examine the factors affecting the construction productivity, Dai et al (2007) There are studies focused on reviewing the degree of impact of the important factors to the productivity. Moselhi, Assem and Ei-Rayes (2005) investigated the impact of change orders on construction productivity and introduced a new neural network model for quantifying the impact.…”
Section: Previous Studiesmentioning
confidence: 99%